(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This study examines teachers perception of punishment as control methods for secondary school students in Oredo Local Government Area of Edo State the rate of indiscipline amongst students in our secondary schools has assumed an alarming magnitude which has occasioned or elicited various control methods as perceived by teachers. The research design adopted was descriptive. The finding of the study revealed that, there is no significant difference between the professional training of a teacher in the perception on the enforcement of punishment by the teacher due to sex. Data was analyzed using descriptive, frequency count and t-test of mean difference statistics with SPSS. The study recommends that opportunities should be made available for both serving teachers and principals to attend in service training programmes, seminars and workshops on the control of students behaviour and punishment. At every level in the course of training a teacher should have some aspects of the legal implication of teachers actions and behaviour should be taught in order to minimize the rate of litigation by parents and students against school authorities.